2021
DOI: 10.1038/s41598-021-89470-3
|View full text |Cite
|
Sign up to set email alerts
|

Multiple DNA marker-assisted diversity analysis of Indian mango (Mangifera indica L.) populations

Abstract: Arbitrary (65 RAPD, 25 ISSR, 23 DAMD), gene-targeted (22 SCoT, 33 CBDP) and co-dominant sequence specific (40 SSR) markers were used individually, or in combinations, to examine the genetic variability within and among 70 selected Indian mango genotypes based on geographic origin (East India, West India, North India, South India) and fruit status (Selection, Hybrid, Landrace). The highest genetic variability was demonstrated by the East Indian populations, followed by those from South India, West India, and No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 65 publications
(61 reference statements)
0
9
0
Order By: Relevance
“…Due to both high genetic diversity and consistent amplification, ITS is a barcoding region that has been selected and used by many previous studies on the identification and investigation of the relationship among a group of taxa on many different subjects [31][32][33] . On the contrary, the SCoT product is amplified from a non-specific single primer [4][5][6][7][8] , so the appearance of bands will also vary significantly among other taxa and components of primer sets. In another way, from the practical study, we also found that the reliability of the SCoT technique also depended on subjectively reading the bands.…”
Section: A Comparison Of Barcoding and Scot Techniquementioning
confidence: 99%
“…Due to both high genetic diversity and consistent amplification, ITS is a barcoding region that has been selected and used by many previous studies on the identification and investigation of the relationship among a group of taxa on many different subjects [31][32][33] . On the contrary, the SCoT product is amplified from a non-specific single primer [4][5][6][7][8] , so the appearance of bands will also vary significantly among other taxa and components of primer sets. In another way, from the practical study, we also found that the reliability of the SCoT technique also depended on subjectively reading the bands.…”
Section: A Comparison Of Barcoding and Scot Techniquementioning
confidence: 99%
“…used after crossing Maduri yellow watermelon with Princess pomegranate red watermelon, to produce orange watermelon hybrids, using 4 PCR-ISSR primers to determine monomorphic and polymorphic to cross orange water melon hybrids with several types of water melon to produce quaternary hybrids, the prefixes gave 36 bands, of which 17 were polymorphic, while 19 were monomorphic. Jena and Chand (16) reported that the increased polymorphism between primers used is due to the amplification of genomic regions with high genetic variance between samples. Used 11 ISSR technology primers to find genetic diversity among 38 types of red watermelon, as 89 different bands, the studied species were divided into 4 groups, the study showed that there is no correlation between the results of molecular indicators with phenotypes, and this is due to diversity, high genetics and the influence of environmental factors (32).…”
Section: Introductionmentioning
confidence: 99%
“…The combination of SCoT+CBDP markers proved to be more effective than the combination of RAPD+ISSR+DAMD markers for evaluating diversity among populations grouped based on geographical locations or fruit status. 160 The usefulness of the SSR markers in the identification of genotypes and estimation of their genetic variability was demonstrated in mangoes. 161,162 Genetic Linkage Maps.…”
Section: ■ Proteome Analysis Of Mango Fruitsmentioning
confidence: 99%